Imagining Policies: European Integration and the European Minority Rights Regime. Issue 1 (2nd January 2016) - Nancheva, Nevena
Abstract: Minority regulation in the EU has come under attack as ineffective and problematic. With the rise of nationalism, racism and xenophobia in Europe and the challenged role of Europeanization, minority/majority relations in the EU may become increasingly problematic. This article argues an inherent incompatibility between what is held as a European standard of minority rights and the dynamics of integration. On the basis of a historical and discursive analysis of the EU minority regime and its normative relationship to integration this article demonstrates how a reifying, state-centric, security-bound conceptualization of national minorities deeply influenced by the theory and practice of nationalism reinforces the logic of nationalism from within the European project. It suggests that a lack of imagination in the study and practice of national minority regulation has prevented the conception of minority policies compatible with the unique normative context of integration as supranational governance and a shared community. Instead of attempting to reproduce the best practices of minority protection invented within the logic of nationalism, Europeanization should categorically move away from them. This would enable it to re-affirm itself as a project of post-national belonging that acknowledges and accommodates the complex dynamics of identity maintenance of post-modernity.